2005
DOI: 10.1128/mcb.25.6.2085-2094.2005
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Genome-Wide Mapping of Transposon Integration in Mammals

Abstract: The Sleeping Beauty (SB) transposon is an emerging tool for transgenesis, gene discovery, and therapeutic gene delivery in mammals. Here we studied 1,336 SB insertions in primary and cultured mammalian cells in order to better understand its target site preferences. We report that, although widely distributed, SB integration recurrently targets certain genomic regions and shows a small but significant bias toward genes and their upstream regulatory sequences. Compared to those of most integrating viruses, howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
257
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(279 citation statements)
references
References 65 publications
21
257
1
Order By: Relevance
“…Furthermore, SB transposon integrations occur in genomic safe harbors, defined by five criteria32, 33 (Figure 7C), at about 25% (Figure 7D). These results are in good agreement with numerous previous studies, which established a close-to-random insertion profile for the SB system in human cells 34, 35, 36, 37…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, SB transposon integrations occur in genomic safe harbors, defined by five criteria32, 33 (Figure 7C), at about 25% (Figure 7D). These results are in good agreement with numerous previous studies, which established a close-to-random insertion profile for the SB system in human cells 34, 35, 36, 37…”
Section: Resultssupporting
confidence: 93%
“…In contrast to the genomic integration profile of retroviral systems and other transposon systems ( piggyBac and Tol2 ), which show integration preferences for actively transcribed genes,51, 52, 53 SB -based integration is random 37, 54. Compared to computationally generated control datasets, SB100X -mediated genomic integration of the PEDF gene delivered by the pFAR4 vector into primary human RPE cells showed a close-to-random profile.…”
Section: Discussionmentioning
confidence: 87%
“…One of the advantages of SB transposon vectors is the random integration profile (Liu et al 2005;Staunstrup et al 2009;Yant et al 2005). Thus, SB vectors are less likely to target genes but may be more vulnerable to transcriptional silencing when inserted in heterochromatin.…”
Section: Discussionmentioning
confidence: 99%
“…SB was genetically reconstructed from fossil elements in the genome of salmoid fish (Ivics et al 1997) and is actively mobilized in cells derived from a variety of vertebrate species . SB-derived vectors efficiently jump from plasmid DNA introduced into cells to chromosomal DNA and are inserted without particular preference for actively transcribed genes (Liu et al 2005;Yant et al 2005). The element has been explored for the use in therapeutic gene transfer (Izsvak and Ivics 2004;Liu et al 2006;Mates et al 2009;Mikkelsen et al 2003;Ohlfest et al 2004;Singh et al 2008;Yant et al 2000) and is widely used as a tool in animal transgenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, it is used for long-term expression in transgenesis and insertional mutagenesis in vertebrates Largaespada et al, 2005). In addition, an analysis of 1336 inserts in primary and cultured mammalian cells has demonstrated that SB integration exhibits less preference for transcriptional units and/or their promoters compared with retroviruses (Yant et al, 2005). Therefore, the SB system appears to be an ideal non-viral vehicle for production of transgenic animals and potential genome-wide mutagenesis due to its relative high activity, large cargo capacity and less integration site preference.…”
Section: Introductionmentioning
confidence: 99%